A framework to investigate fishery dynamics and species size and age spatio-temporal distribution patterns based on daily resolution data: a case study using Northeast Atlantic horse mackerel. (28th October 2020) - Azevedo, Manuela; Silva, Cristina
Abstract: In this study, we present an innovative framework to obtain essential biological knowledge on exploited populations, based on fine scale spatio-temporal resolution in biological and fishery data. The framework uses species sales notes by commercial size category, the length and age composition of commercial sizes from onshore sampling and the fishing ground and fishing effort from vessel monitoring system records. We apply the framework to horse mackerel ( Trachurus trachurus ), one of the most important commercially exploited stocks throughout the Northeast Atlantic, using data collected during 2017 in Portuguese waters. We show that high-resolution mapping of the species annual landings by commercial size category and age group can already reveal different distribution patterns by life stage. We further examined, with daily resolution, the variability in the proportion of adult fish by trip, finding differences along the coast and a seasonal pattern indicating that spawning occurred mainly over the slope and adult horse mackerel dominated in the South zone over the year. The framework can be applied to an extended stock area and for several years to investigate migration patterns across areas as well as intra- and inter-annual changes in the species overall distribution. In addition, its application on a trip basis for the species ensemble landed can provide overriding information for the accuracy of mixed fisheries models and management.